The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.11606/issn.2176-7262.v51i4p237-246
|View full text |Cite
|
Sign up to set email alerts
|

Desfechos clínicos dos pacientes submetidos à intervenção coronária percutânea com stent bioabsorvível eluidor de everolimus

Abstract: Modelo: Estudo descritivo, transversal, retrospectivo. Objetivo: Identificar desfechos clínicos e a prevalência de uso da dupla antiagregação plaquetária (DAP) 30 dias e 12 meses após implante de stent bioabsorvível eluidor de everolimus (BVS). Metodologia e casuística: Foram coletados e analisados de maneira descritiva dados referentes a antecedentes clínicos, procedimento, resultados pós-procedimento e complicações intra-hospitalares, acompanhamento e antiagregação plaquetária 30 dias e um ano após implante … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…All articles included were published between 2000 and 2020, referring to studies conducted between 1993 and 2017. Most studies were conducted in Brazil [ 3 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 ]. Six studies were conducted in Argentina [ 59 60 61 62 63 64 ], four in Chile [ 65 66 67 68 ], four in Colombia [ 69 70 71 72 ], three in Uruguay [ 73 74 75 ] and two were multi-country studies conducted in Argentina, Brazil, Chile and Colombia [ 12 ] and Brazil and Suriname [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All articles included were published between 2000 and 2020, referring to studies conducted between 1993 and 2017. Most studies were conducted in Brazil [ 3 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 ]. Six studies were conducted in Argentina [ 59 60 61 62 63 64 ], four in Chile [ 65 66 67 68 ], four in Colombia [ 69 70 71 72 ], three in Uruguay [ 73 74 75 ] and two were multi-country studies conducted in Argentina, Brazil, Chile and Colombia [ 12 ] and Brazil and Suriname [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Half of them reported that medication use was low [59,62,[76][77][78] or insufficient compared to guideline recommendations [2,12,48,61,79]. Other articles reported that cardioprotective medication use was adequate or high [32,60,66,67,73,75], or in line with guideline recommendations [38,65,80].…”
Section: Guideline Compliancementioning
confidence: 99%